How gender affects the pharmacotherapeutic approach to treating psychosis: a systematic review - Lange, Bettina; Leweke, F. Markus (Expert opinion on pharmacotherapy, 2017)
Introduction: The effectiveness, effective dosages and side effect profiles of antipsychotic medication differ significantly between the sexes. Areas covered: We present a systematic review of gender-differences in the treatment of psychosis focusing on randomized, controlled trials and meta-analyses. Expert opinion: Despite many years of research, the database on gender-differences affecting the pharmacotherapeutic approach to treating psychosis is insufficient. Currently, the US National Institute of Health encouraged the enrolment of female participants in federally supported phase III clinical trials to increase the data available of female patients. Emerging evidence points to a superior antipsychotic response in women, with men requiring higher dosages. In general, women metabolize drugs differently, resulting in side effects occuring more frequently when compared to men. In any case, women require electrocardiograms or bone density scans as well as diabetes and cardiovascular workups when treated with antipsychotics. Dose adjustments during the menstrual cycle (e.g. to raise antipsychotic doses premenstrually) should be considered. First-generation antipsychotics, drugs that are known to prolong QTc interval and increase prolactin levels should be avoided in postmenopausal female patients. Furthermore, the effects of antipsychotics during pregnancy and breastfeeding have been investigated insufficiently, and more research is urgently needed.